Dark tourists: profile, practices, motivations and wellbeing - Magano, José (2022)
This work aims to address whether knowing what dark tourism is (or not) impacts rumination on sadness, self-hatred, hostility, psychological vulnerability, and tourist wellbeing, as well as practices and motivations for dark tourism. A quantitative approach, based on a survey of 993 respondents, reveals that women and more educated participants know more about dark tourism; people who know what dark tourism is have visited more Holocaust museums, sites of human tragedy and natural disasters, concentration camps, and prisons; show more curiosity, need to learn and understand, and need to see morbid things. A model was found showing that gender, age, know/do not know dark tourism, and motivations (curiosity, the need to learn, the need to understand, and pleasure) explained 38.1% of a dark tourism practice index. Most findings also indicate that rumination on sadness, self-hatred, hostility, and psychological vulnerability are associated with darker practices. Greater wellbeing was not found in participants who knew in advance what dark tourism was. Interestingly, participants who visit tragic human sites present higher values in hostility and tourist wellbeing than those who do not. In summary, people who visit more dark places and score higher on negative personality characteristics have higher values of tourist wellbeing.